Analisis Potensi Pengembangan Agrowisata di Subak Batan Wani Desa Sading Kecamatan Mengwi Kabupaten Badung - PRATIWI, NI MADE WAHYU TRI; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p38, 2022)
The Analysis of Agrotourism Development Potential in Batan Wani Subak (irrigation system), Sading Village, Mengwi, Badung Regency Agrotourism is defined as a combination of agriculture and tourism. The potential of rice fields in Batan Wani Subak (irrigation system) can be applied as an opportunity to develop agritourism, yet there are conditions that need to be filled, namely the 4A aspects such as attraction, accessibility, amenity, and ancillary. The aims of this study were to identify the potential in Subak Batan Wani in developing Agrotourism also strategies in developing its Agrotourism. The data was analyzed by descriptive-qualitative method and SWOT analysis. Based on the research results, the potential in the Subak Batan Wani that can be developed as agrotourism includes, there are accessibility (affordability), amenity (facilities and infrastructure) travel agents also attractions (attractions) culture, agrarian and natural tourist attractions in the form of air in the cool and beautiful Subak area which is the strengths and weaknesses that there is no unique agricultural activity.  The opportunity factor for the Kereban Langit Temple tourist attraction and the mepeed tradition (walking and in hand) in the village, while the threat factor that must be anticipated was the occurrence of tourist density.  An alternative strategy that can be employed is the S – O strategy, namely promoting through social media such as Instagram, Facebook related to the location of Batan Wani subak and utilizing the tracking on Subak, providing shops, washing hands, checking body temperature considering to the current Covid-19 pandemic, and forming a tourism agency.Suggestions are needed for the further development namely by making unique and distinctive attractions, in example making photo spots.  Support from other parties in the development of Agrotourism in Batan Wani subak, especially the government agencies.